2001
DOI: 10.1104/pp.010196
|View full text |Cite
|
Sign up to set email alerts
|

Brachypodium distachyon. A New Model System for Functional Genomics in Grasses

Abstract: A new model for grass functional genomics is described based on Brachypodium distachyon, which in the evolution of the Pooideae diverged just prior to the clade of "core pooid" genera that contain the majority of important temperate cereals and forage grasses. Diploid ecotypes of B. distachyon (2n ϭ 10) have five easily distinguishable chromosomes that display high levels of chiasma formation at meiosis. The B. distachyon nuclear genome was indistinguishable in size from that of Arabidopsis, making it the simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
223
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 452 publications
(229 citation statements)
references
References 62 publications
5
223
0
1
Order By: Relevance
“…The species of the genus Brachypodium have small chromosomes of variable number (x = 5, 7, 8, 9 or 10), making them unusual among the members of the Pooideae, which tend to have large chromosomes and base number of 7 (Shi et al 1993;Draper et al 2001;Hasterok et al 2004Hasterok et al , 2006Idziak and Hasterok 2008;Garvin et al 2008). Although ecotypes of B. distachyon with 10, 20 and 30 chromosomes have been described, some authors have indicated that these numbers do not represent a simple autopolyploid series (Robertson 1981).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The species of the genus Brachypodium have small chromosomes of variable number (x = 5, 7, 8, 9 or 10), making them unusual among the members of the Pooideae, which tend to have large chromosomes and base number of 7 (Shi et al 1993;Draper et al 2001;Hasterok et al 2004Hasterok et al , 2006Idziak and Hasterok 2008;Garvin et al 2008). Although ecotypes of B. distachyon with 10, 20 and 30 chromosomes have been described, some authors have indicated that these numbers do not represent a simple autopolyploid series (Robertson 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Brachypodium is therefore seen as a ''bridge'' between rice and the Triticeae tribe. Various molecular phylogenetic analyses have shown that Brachypodium diverged from the ancestral stock of Pooideae immediately prior to the radiation of the modern ''core pooids'' (Catalan et al 1997;Catalan and Olmstead 2000;Draper et al 2001). It is also ancestral, but equally related to, Avena and Triticum (Kellogg 2001;Huo et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachypodium spp. is a useful model grass because of its small, completely sequenced diploid genome (International Brachypodium Initiative, 2010), simple growth requirements, large collection of accessions, inbreeding nature, and high rate of recombination (Draper et al, 2001;Vogel et al, 2006Vogel et al, , 2009Opanowicz et al, 2008;Filiz et al, 2009;Brkljacic et al, 2011;Huo et al, 2011;Mur et al, 2011). All of these characteristics make Brachypodium spp.…”
mentioning
confidence: 99%
“…These changes can alter the functional relationships between orthologous genes in wheat and rice, making it difficult to predict the function in one species based on the function of the orthologue in the other species. Brachypodium is emerging as a better model system for wheat because of the more recent divergence of these two lineages (35-40 million years) compared to the wheat-rice divergence (Draper et al 2001;Hasterok et al 2006;Vogel et al 2006). Although the successful sequencing of Brachypodium will most likely be a valuable resource for wheat, the first comparative genomic studies are showing multiple alterations of colinearity between these two genomes (Bossolini et al 2007;Valarik et al 2007) suggesting that a final validation of gene function directly in wheat will still be necessary.…”
Section: Introductionmentioning
confidence: 99%